Using e-mail aesthetic messages in the mathematics classroom: Some insights for teacher education - Nyaumwe, Lovemore J (South African Journal of Higher Education, 2016)
The purpose of this paper was to show how e-mail aesthetic texts can be used in the mathematics classroom. Kilpatrick’s (2001) five strands of conceptual understanding, procedural fluency, adaptive reasoning, strategic competency and productive disposition were used as theoretical framework for showing how the messages can be used to develop learners’ mathematical proficiency. The e-mail text on the primitive Hindu-Arabic numerals was used to illustrate how the current numerals got their shapes, the Chinese multiplication style used to show how learners can verify products obtained using the conventional method, a calendar problem used to show how adaptive reasoning can be developed and a problem on borrowing used to show how learners can develop strategic competency. Based on the utility and motivational potential of these e-mail aesthetic messages, teacher education is challenged to produce millennium-compliant socially responsible teachers who can utilise the technology available to learners to develop understanding of mathematical concepts.